Psychological disturbances in adolescents with acute voluntary poisoning - Viorela Nitescu; Dora Boghitoiu; Coriolan Ulmeanu (Amaltea Medical Publishing House, 2019)
Objective. The present study has two main objectives: to evaluate the psychological characteristics of adolescents with voluntary acute poisoning in a pediatric toxicology department and to estimate the role of psychological evaluation in the management of these patients. Material and method. The study includes the retrospective analysis of all patients with voluntary acute intoxication, admitted to our clinic between October 1, 2017 and September 30, 2018. The following criteria were considered: age, gender, number of hospitalizations with this diagnosis and psychological evaluation. performed during hospitalization. Results. During the mentioned period, in the Toxicology and Intensive Care Department of the Emergency Clinical Hospital for Children "Grigore Alexandrescu" in Bucharest, 181 patients were admitted with the diagnosis of voluntary acute poisoning, aged between 10 and 18 years. There was a similar percentage of girls compared to boys (58.1% compared to 41.9%), and most patients (n = 137, 75.7%) were from urban areas. Of the total number of patients 22 (12.1%) had two or more hospitalizations with the diagnosis of voluntary acute intoxication. In 13 cases (7.2%), patients were known to have previous psychiatric disorders: 8 patients with depression, 2 with behavioral disorder and 3 with disorders associated with chronic substance abuse. Analyzing the results of the psychological evaluation in these patients we found that the main psychological disorder was the emotional reaction, being identified in 98 patients (54.1%). The suicide attempt was identified in only 31 patients (17.1%) of whom only 10 received the transfer recommendation in a psychiatric clinic. Conclusions. Psychological evaluation of patients with acute voluntary intoxication is essential during hospitalization in the toxicology section to identify real psychological problems. Emotional reaction is the main psychological disorder in patients with acute voluntary intoxication. The actual suicide attempt is found only in a relatively small number of patients, in our study being diagnosed only at 17% of the total voluntary acute poisoning.